2014
DOI: 10.1007/s00415-014-7476-7
|View full text |Cite
|
Sign up to set email alerts
|

ANO10 mutations cause ataxia and coenzyme Q10 deficiency

Abstract: Inherited ataxias are heterogeneous disorders affecting both children and adults, with over 40 different causative genes, making molecular genetic diagnosis challenging. Although recent advances in next-generation sequencing have significantly improved mutation detection, few treatments exist for patients with inherited ataxia. In two patients with adult-onset cerebellar ataxia and coenzyme Q10 (CoQ10) deficiency in muscle, whole exome sequencing revealed mutations in ANO10, which encodes anoctamin 10, a memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 13 publications
1
67
0
Order By: Relevance
“…The coenzyme Q10 deficit observed in case report 1 confirmed that ANO10 mutations can induce this phenotype with metabolic disorder [4] . However, supplementation did not improve ARCA3 symptoms in our patient.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The coenzyme Q10 deficit observed in case report 1 confirmed that ANO10 mutations can induce this phenotype with metabolic disorder [4] . However, supplementation did not improve ARCA3 symptoms in our patient.…”
Section: Discussionmentioning
confidence: 54%
“…Seven ARCA3 patients presented cognitive decline (27%) [3,6] and between 2 and 4 presented epilepsy (7-15%) [4,5] out of the 26 cases reported. In addition to the previous 2 epileptic ANO10 patients (one confirmed [4] and one suspected [5] ) in the literature, we reported 2 new epileptic ARCA3 patients. No epileptogenic origin other than ARCA3 was found in case report 1.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…and Savarese et al 130 for TMEM16E, from Suzuki et al 40 and Castoldi et al 93 for TMEM16F, and Vermeer et al 131 and Balreira et al 132 for TMEM16K Figure 3 The molecular mechanism for PtdSer exposure in cells with high Ca 2+ -concentration. The flippase comprised of P4-ATPase (ATP11A or ATP11C) and CDC50A, and a Ca 2+ -dependent scramblase (TMEM16F) are schematically shown.…”
mentioning
confidence: 99%